Bodily Passions: Physiognomy and Drama in Giovan Battista Della Porta - Refini, Eugenio (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2017)
This article explores the intersections of physiognomic knowledge and drama in the works of Neapolitan naturalist and playwright Giovan Battista Della Porta (1535–1616). It first looks at references to theatre—classical drama in particular—in Della Porta’s writings on physiognomy, thus showing that Latin comic plays provided the naturalist with a gallery of stock characters able to summarize the alleged interdependence of physical and moral traits. The article then analyzes the various ways in which Della Porta—who was a prolific author of comedies—brought his physiognomic expertise into his own experience as a playwright. The study of these two different perspectives on the relation between physiognomy and drama reveals that, far from being a direct translation of physiognomic theories, Della Porta’s dramatic production deploys an ironic and almost paradoxical take on physiognomy that aims to challenge (if not actually subvert) the very principles of the discipline.